Integrated management of cotton aphid, Aphis gossypii on roof-planted eggplant, Solanum melongena - Alim, Md Abdul; Naher, Habibun; Habib, AHM Shafiullah; Islam, Md Aminul (Bangladesh Journal of Zoology, 2015)
Prevalence and integrated management of cotton aphid, Aphis gossypii Glover (Homoptera: Aphididae) were studied on four varieties of roof planted eggplant (Solanum melongena L.) Along the sixteen weeks study period highest incidence of aphids (1959.17.17±172.44/plant) on eggplant variety of Blackboy were recorded at 16th week (last week of February, 2013) and the lowest incidence (12.83±8.68/plant) was recorded on the eggplant variety Singnath at 13th week (first week of February, 2013). The treatment having combination of 2g Neem seed kernel extract (NSKE) + ½gm detergent+100ml water) was most effective followed by a treatment of 2g NSKE+100ml water and 1g NSKE+100ml water in reducing the rate of aphid infestation. Eggplant variety Green round showed comparatively higher resistance in all aspects (from leaf and fruit infestation) followed by variety Muktakeshi and Black boy. Bangladesh J. Zool. 43(1): 19-26, 2015